Neither stretching nor postactivation potentiation affect maximal force and rate of force production during seven one-minute trials - Bazett-Jones, D. M. (UW-L Journal of Undergraduate Research, 2004)
Warm-up involves different factors and is implemented in multiple fields and applications. In athletics, it is an essential aspect of preparation. Four specific different warm-ups were randomly investigated in this study. PURPOSE: The purpose of this investigation was to compare the effects of stretching versus a heavy squat (potentiation) versus a loaded jump squat (potentiation) on subsequent maximal force and rate of force development capabilities in an isometric squat. METHODS: Ten male collegiate football and track & field athletes (9 & 1 respectively) participated as subjects in this study. Subjects were tested during four separate sessions that involved seven isometric squat trials on a force plate at one-minute intervals to determine maximal force (MF) and rate of force development (RFD) values. The sessions included a five-minute bike warm-up followed by nothing (control), a heavy squat set (3 reps at 90% 1RM), a loaded jump squat set (9 reps at 30%), or a stretching protocol (3 reps of 30 seconds on each leg; quadriceps and gluteals). RESULTS: MF and RFD in the isometric squat was not significantly different following any of the four conditions (C=3160.7+205.0 N, S=3092.2+188.2, JS=3268.9±207.6, HS=3172.7+190.3; C=167.1+19.3 N/s, S=153.1+20.9, 164.6+19.9, HS=172.0+20.9). CONCLUSION: Some insignificant results show that the loaded jump squat protocol may increase maximal force and that stretching may decrease this variable, with a larger sample size. Future experiments investigating the possibility of potentiation should involve loaded jump squats. Stretching seems to be detrimental to performance in athletic activities that require maximal force production.